The Relationship between Knowledge Level and Work Period on Compliance with the Use of Personal Protective Equipment (PPE) among DNT Workers at PT. Cast Inspection And Engineering - Al Awwarij, Achmad Sakhowi (Future Science, 2025)
The application of Occupational Health and Safety (OHS) is a crucial aspect in the sustainability of industrial operations to protect workers from the risks of accidents. This research aims to empirically analyze the influence of knowledge level and work experience on the compliance of using Personal Protective Equipment (APD) among Non-Destructive Testing (NDT) operators at PT. Cast Inspection and Engineering. This research uses a quantitative method with a cross-sectional study design. The research population includes all 60 NDT operators, using a total sampling technique. Data were collected through structured questionnaires and observations, then analyzed using the Chi-Square statistical test. The research results indicate that the majority of respondents have low knowledge (53.3%) and less than 5 years of work experience (75.0%), with a non-compliance rate in the use of PPE of 58.3%. There is a significant relationship between knowledge level and compliance with PPE use (p-value < 0.05), where workers with low knowledge have a 4.164 times greater risk of non-compliance. Furthermore, there is a significant relationship between work experience and compliance (p-value < 0.05), where work experience above 5 years correlates positively with increased compliance. It can be concluded that technical knowledge and field experience are key factors in safety behavior. It is recommended that companies improve educational programs and mental coaching, especially for new employees, to achieve the target of zero accidents